2019
DOI: 10.1155/2019/2501847
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modified Sini Decoction on Survival Rates of Patients with Hepatitis B Virus Related Acute-on-Chronic Liver Failure

Abstract: Aim of the Study.To verify the effect of modified sini decoction on patients with hepatitis B virus related acute-on-chronic liver failure.Materials and Methods.A retrospective cohort study was conducted. Patients who had been treated with modified sini decoction and standard comprehensive internal medicine were assigned to an observation group, and patients who had been treated with standard comprehensive internal medicine were selected as a control group. The total bilirubin (TBIL), albumin (ALB), alanine am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Millions of years of coevolution have shaped the symbiotic relationship between humans and microorganisms, in which the gut bacteria play a crucial role in the metabolism of human nutrients, while the human gut provides a nutrient rich environment for the bacteria. Therefore, an imbalance in the gut microecology leads to the occurrence or aggravation of disease [32][33][34][35][36][37]. Dysfunction of the intestinal epithelium, dysfunction of the immune system, and translocation of enteropathogenic bacteria are considered to be the key factors leading to infectious complications and multiple organ dysfunction syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of years of coevolution have shaped the symbiotic relationship between humans and microorganisms, in which the gut bacteria play a crucial role in the metabolism of human nutrients, while the human gut provides a nutrient rich environment for the bacteria. Therefore, an imbalance in the gut microecology leads to the occurrence or aggravation of disease [32][33][34][35][36][37]. Dysfunction of the intestinal epithelium, dysfunction of the immune system, and translocation of enteropathogenic bacteria are considered to be the key factors leading to infectious complications and multiple organ dysfunction syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that the potential therapeutic effect of SNRS on ALF might be through promoting the expression of PPARα and increasing the level of ATP in liver tissue, inhibiting the necrosis of liver cells, reducing liver cell damage, and improving liver function (He et al, 2022). Our previous studies also found that modified sini decoction could protect the liver function and improve the survival rates of patients with hepatitis B virus related acute-on-chronic liver failure (Luo et al, 2019). Moreover, a study have shown that sini decoction inhibits tumor progression and enhances anti-tumor immune response in mouse colon cancer model (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 98%
“…Sini Decoction Plus Ginseng Soup (SNRS) was first described in “Treatise on Febrile Diseases” written by Zhong‐jing Zhang, which consists of four herbs: Zhi Gan Cao (licorice), Gan Jiang (dried ginger), Fu Zi (aconite lateral root) and Ren Shen (ginseng). Some previous studies have found that sini decoction can treat a variety of liver diseases and cancer (Chen et al., 2023; He et al., 2022; Luo et al., 2019). Our previous studies demonstrated that SNRS inhibited hepatocyte necrosis, reduced hepatocyte damage, and improved liver function in mice with acute liver failure (He et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Millions of years of coevolution have shaped the symbiotic relationship between humans and microorganisms, in which the gut bacteria play a crucial role in the metabolism of human nutrients, while the human gut provides a nutrient rich environment for the bacteria. Therefore, an imbalance in the gut microecology leads to the occurrence or aggravation of disease [24][25][26][27][28][29] . Dysfunction of the intestinal epithelium, dysfunction of the immune system, and translocation of enteropathogenic bacteria are considered to be the key factors leading to infectious complications and multiple organ dysfunction syndromes.…”
Section: Introductionmentioning
confidence: 99%